The new online banking consumer. An occasional user or a new full-time customer - Covadonga Gijón; Fernando Fernández-Bonilla; Aurora Ruíz-Rúa (International Telecommunications Society (ITS), 2023)
This paper studies the determinants of individuals' propensity to use electronic banking and the impact of the pandemic on that. We found that the variables with the greatest significant weight for participation are the variables of the Technology Acceptance Model (TAM). Furthermore, we observe changes in e-banking after the pandemic due to sociodemographic variables with increasing relevance of gender and income variables, indicating that the gender and economic digital divide has increased as well. The educational level variable has decreased, reducing the educational gap in the analysis of the digital divide. However, the most relevant variables are digital skills and frequency of internet use, which have a much stronger influence on e-banking adoption. Finally, based on the findings presented above and below, some policy recommendations are provided.
Keywords: 330; traditional banking; online banking; consumers; survey data; econometric models